New coronavirus infection in a child with severe secondary immunodeficiency associated with hematopoietic stem cell transplantation against the background of acute lymphoblastic leukemia - S. M. Bezrodnova; N. A. Yatsenkо; G. M. Sirazhov; Yu. N. Kashina (Детские инфекции (Москва))
Children are more likely to have asymptomatic and mild forms of novel coronavirus infection, as well as a more favorable outcome of the disease compared to adult patients. Children account for about 15% of all cases of COVID-19 recorded in the country. There are more and more reports of severe and even fatal cases of a new coronavirus infection in children. The development of severe forms of COVID-19 is typical for children at risk. Of particular interest are special groups of pediatric patients, such as children with immunodeficiencies of various etiologies.A clinical case of a new coronavirus infection with a fatal outcome in a 10-year-old child with severe secondary immunodeficiency associated with hematopoietic stem cell transplantation against the background of acute lymphoblastic leukemia is presented.